PENDIDIKAN KELUARGA SAKINAH DALAM TAFSIR AL-MARAGHI - As'ad As'ad (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Family or household is a humanitarian system that the urgency based on theIslam. Family has become a necessity of relationship between the elements of the family.Relationship that occur within a family should be a harmonious relationship, cool, andcomfortable, filled with compassion, so that the family get some peace and tranquility. Toachieve calm and serene family can not be separated from the family element itself,which is called by Keluarga Sakinah. Ahmad Mustafa al-Maraghi has explained in tafsiral-Maraghi , sakinah is very closely related to the family that is in Al-Qur‟an ar-Rumverse 21 on sentence (Litaskunu Ilaiha) so that you feel at ease with him (husband andwife).Keywords: Pendidikan, Keluarga Sakinah, Tafsir al-Maraghi.